Intracardiac Fibrinolysis and Endothelium Activation Related to Atrial Fibrillation Ablation with Different Techniques - Orsolya Hajas; Zsuzsa Bagoly; Noémi K Tóth; Réka Urbancsek; Alexandra Kiss; Kitti B Kovács; Ferenc Sarkady; Attila Nagy; Anna V. Oláh; László Nagy; Marcell Clemens; László Csiba; et al. (Cardiology Research and Practice)
Objective. The effect of pulmonary vein isolation (PVI) on fibrinolytic and endothelial activation with currently applied periprocedural anticoagulation has not been explored. We measured markers of fibrinolysis and endothelium activation before and after PVI with the second-generation cryoballoon (Cryo), pulmonary vein ablation catheter (PVAC-Gold), and irrigated radiofrequency (IRF). Methods. Markers of fibrinolysis and endothelium activation in left atrial (LA) blood samples were measured in 31 patients before and after PVI (Cryo:10, PVAC-Gold: 7, IRF: 14). Periprocedural anticoagulation included uninterrupted vitamin K antagonist and iv heparin (ACT≥300 sec) during LA dwelling. Results. Levels of D-dimer (median; interquartile range, mgFEU/L) increased with all techniques (PVAC: 0.34; 0.24–0.50 versus 0.70; 0.61–1.31; p=0.0313, Cryo: 0.33; 0.28–0.49 versus 0.79; 0.65–0.93; p=0.0078; IRF 0.33; 0.21–0.44 versus 0.83; 0.56–1.21; p=0.0001). PAP complex level (ng/ml) increased after Cryo (247.3, 199.9–331.6 versus 270.9, 227.9–346.7; p=0.0020) and IRF (265.3; 202.0–800.1 versus 325.6, 250.2–701.9; p=0.0166), but not after PVAC (p=0.2969). PAI-1 activity (%) decreased with the PVAC (1.931; 0.508–3.859 versus 0.735, 0.240–2.707; p=0.0313) and Cryo (0.361; 0.080–1.575 versus 0.378; 0.111–0.915; p=0.0313). A similar trend was observed with IRF (p=0.0676). Both VWF antigen levels and FVIII activity increased after PVI with all the 3 techniques. The levels of soluble VCAM-1 (ng/ml) did not change after PVAC procedures, but increased after Cryo (542, 6; 428.5–753.1 versus 619.2; 499.8–799.0; p=0.0005) and IRF (679.3; 505.0–744.7 versus 770.9; 631.9–894.0; p<0.0001). Conclusion. PVI with contemporary ablation techniques and periprocedural antithrombotic treatment induces coagulation and endothelium activation of similar magnitude with different ablation methods.